Deeper insights into effect of activated carbon and nano-zero-valent iron addition on acidogenesis and whole anaerobic digestion. (March 2021) - Wang, Ruming; Li, Chunxing; Lv, Nan; Pan, Xiaofang; Cai, Guanjing; Ning, Jing; Zhu, Gefu
Graphical abstract: Highlights: Both AC and nZVI increased the production of VFAs in acidogenesis. nZVI strengthened the formation of formic and acetic acids in acidogenesis. nZVI is superior to AC on the enhancement of methane in whole AD. Methanobacterium was selectively enriched with nZVI addition. Mechanism of AC and nZVI on acidogenesis and whole AD was analyzed and compared. Abstract: Conductive materials presented promising advantages for enhancing anaerobic digestion (AD) performance. This study evaluated the effects of activated carbon (AC) and nano-zero-valent iron (nZVI) on the acidogenesis and whole AD to explore their potential mechanisms. AC increased the content of lactic and propionic acids in acidogenesis. nZVI increased the production of formic acid, acetic acid and H2 in acidogenesis, thus significantly promoted the methane yield in the whole AD. Mechanism exploration proved that AC enriched Trichococcus, and norank_f__Bacteroidetes_vadinHA17, and then improved the activity of enzymes involved in the production of lactic and propionic acids. nZVI buffered the pH to increase the activity of pyruvate formate-lyase (PFL) in formic acid production. Furthermore, nZVI enriched the Methanobacterium which use H2 and formic acid as substrate. The research paves pathway for the efficient enhancement of conductive materials added novel AD process.